Pengaruh Model Pembelajaran Problem Based Learning Berbasis Pembelajaran Berdiferensiasi Terhadap Berpikir Kritis Siswa Kelas 4 SDN Pakis V Surabaya - Aisyah, Indira Fitri; Larasati, Diyas Age; Suryandari, Savitri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to determine the effect of the Problem Based Learning model based on differentiated learning on students' critical thinking. This research uses a quantitative approach with a quasi-experimental design (nonequivalent control group design). The population of the study is all 4th-grade students of SDN Pakis V Surabaya for the 2024/2025 academic year, with sample selection using purposive sampling based on students' ability levels (high, medium, low). The research instruments include pretest and posttest questions to measure critical thinking abilities, as well as observation sheets to observe the implementation of learning. The validity of the instruments was tested by expert validators, and reliability was tested using Cronbach's Alpha. Normality and homogeneity tests were also conducted before data analysis using the T-test. The research results indicate a significant effect of the application of the PBL model based on differentiated learning on students' critical thinking. The integration of the PBL model with differentiated learning has proven to be effective in enhancing critical thinking skills among 4th-grade students, particularly in Mathematics. This approach allows for personalized learning, activation of cognitive schemas, active knowledge construction, and metacognitive reflection, which are crucial for facing the challenges of the 21st century.